2016
DOI: 10.1080/15548627.2016.1238551
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced autophagy in pulmonary endothelial cells on exposure to HIV-Tat and morphine: Role in HIV-related pulmonary arterial hypertension

Abstract: Intravenous drug use is one of the major risk factors for HIV-infection in HIV-related pulmonary arterial hypertension patients. We previously demonstrated exaggerated pulmonary vascular remodeling with enhanced apoptosis followed by increased proliferation of pulmonary endothelial cells on simultaneous exposure to both opioids and HIV protein(s). Here we hypothesize that the exacerbation of autophagy may be involved in the switching of endothelial cells from an early apoptotic state to later hyperproliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 71 publications
(101 reference statements)
3
30
0
1
Order By: Relevance
“…It has also been reported that exposure of human pulmonary microvascular endothelial cells to both the HIV-1 Tat protein and morphine resulted in an oxidative stress-dependent increased expression of autophagy markers and increased generation of autophagosomes compared to cells exposed to either agent alone. Intriguingly, treatment of these cells with morphine alone or in combination with HIV-1 Tat inhibited the fusion of autophagosome with the lysosomes [66]. Induction of autophagy by morphine is cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that exposure of human pulmonary microvascular endothelial cells to both the HIV-1 Tat protein and morphine resulted in an oxidative stress-dependent increased expression of autophagy markers and increased generation of autophagosomes compared to cells exposed to either agent alone. Intriguingly, treatment of these cells with morphine alone or in combination with HIV-1 Tat inhibited the fusion of autophagosome with the lysosomes [66]. Induction of autophagy by morphine is cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic increase in autophagy reduces the incidence of oxidative stress and apoptosis that allows the cells to adapt to stress leading to cell survival and uncontrolled proliferation of pulmonary endothelial cells. Therefore, morphine in combination with Tat results in the induction of autophagy in pulmonary endothelial cells that may lead to an increase in severity of angio-proliferative remodeling of the pulmonary vasculature [ 56 ].…”
Section: Hiv Tat and Cardiovascular Diseasesmentioning
confidence: 99%
“…Since the inception of cART, the impact of chronic inflammatory insult by HIV-1 infection has become an important topic; persistent latently and productively infected perivascular macrophage and microglial populations [ 14 , 17 19 ] represent the primary reservoirs for HIV-1 in the CNS [ 20 24 ]. In vivo and in vitro studies focusing on the HIV-1 transactivator of transcription (Tat) protein demonstrate morphine’s exacerbating effects on microglial activation [ 25 29 ], astroglia dysregulation [ 29 32 ], cytokine production [ 33 38 ], and blood-brain barrier (BBB) breakdown [ 13 , 39 , 40 ], with additional effects on oxidative stress [ 33 , 34 , 41 , 42 ], intracellular calcium [ 34 , 37 , 43 ], and neurotoxicity [ 38 , 42 44 ], potentially due to morphine’s action on μ-opioid receptor (MOR)-expressing glia [ 31 , 45 ]. Notably, HIV-1 and HIV-1 proteins, such as Tat, impact opioid gene expression and splicing specificity [ 38 , 46 48 ], potentially mediated through the release of various proinflammatory cytokines, including IL-6, TNF, GM-CSF, and IFN-γ [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%